Amorphophallus: New insights into pollen morphology and the chemical nature of the pollen wall. Issue 1 (2nd January 2017) - Ulrich, Silvia; Hesse, Michael; Weber, Martina; Halbritter, Heidemarie
Abstract: In pollen characters, Amorphophallus is one of the most diverse genera in the Araceae. The present work is a critical survey of contradicting reports on the impact of acetolysis treatment on Amorphophallus pollen, on the chemical nature of the outer pollen wall layer and of electron-dense (dark) granules found within it. Furthermore, we wanted to clarify the pollen polarity and to test conclusions based on different preparation techniques. Pollen morphology of 25 species is investigated by light microscopy, scanning electron microscopy and transmission electron microscopy. Our results show that Amorphophallus pollen is not resistant to acetolysis treatment. The use of different transmission electron microscopy staining methods proved the polysaccharide nature of the outer pollen wall layer and of the granules within it. Moreover, an additional thin surface layer was found in all investigated species. Microspores in early and late tetrad stages show that the less convex side of the microspore is the proximal face and the more convex side the distal face. The extrusion of pollen in strands is illustrated for the first time by light microscopy and scanning electron microscopy. Furthermore, observations of pollen in water showed that in some of the investigated species the pollen wall is shed immediately before pollen tube formation.